Distribution of joint work during walking on slopes among persons with transfemoral amputation. (2nd December 2021) - Bonnet, Xavier; Villa, Coralie; Loiret, Isabelle; Lavaste, François; Pillet, Helene
Abstract: Persons with above-knee amputation have increased energy consumption and greater difficulty in negotiating uphill and downhill slopes. Walking on slopes requires an adaptation of the positive and negative work performed by the joints of the lower limb to propel the center of mass. Modern prosthetic feet and knees can only partially adapt to changes in inclination, and the redistribution of joint work among persons with above-knee amputation is not described in the literature. Level, upslope and downslope walking (at 5% and 12% inclinations) were investigated for twelve subjects with transfemoral amputation fitted with an Energy Storing And Return foot (ESAR) and a Microprocessor controlled Prosthetic Knee (MPK) versus a control group of seventeen asymptomatic subjects. Lower limb joint and individual limb power and work were compared between prosthetic, contralateral and control limbs. The prosthesis dissipates less energy than the joints of the lower limb of the control group when descending the slope, but the demand on the contralateral limb is limited by a lower speed and step length. The huge deficit of positive work produced by the prosthetic ankle cannot be compensated by the residual hip during level and slope ascent which transfers the demand for energy production to the contralateral limb up to 40% on a 12% slope. This study highlights that prosthetic devices (ESAR foot and MPK) for persons with above-knee amputation present some limitations during slope walking that cannot be compensated by the residual hip and increase the work performed by the contralateral limb.